THE EFFECT OF CHAIN SPELLING GAME ON THE STUDENTS’ VOCABULARY MASTERY OF THE EIGHTH GRADE AT SMPN 2 BUKIK BARISAN - Rahmi Rahmi; Eliza; Reflinda Reflinda; Irwandi Irwandi (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This research investigated the challenges faced by eighth grade students at SMPN 2 Kec. Bukik Barisan in the English learning process, especially concerning vocabulary mastery. Identified problems include students’ score were below the minimum completion criteria (KKM). Secondly, some students had difficulty in remembering vocabulary. Next, some students had difficulty in understanding the meaning of the vocabulary. Furthermore, students had difficulty pronouncing English words appropriately. Finally ,teacher still used conventional method when teaching English. So, the purpose of this research is to see the effect of using chain spelling games on students’ vocabulary mastery of eighth grade students at SMPN 2 Kec. Bukik Barisan.This research used true experimental with pretest-posttest research design in experimental and control classes. Researcher used simple random sampling to determined the research sample. The samples of this research were class VIII.A as the experimental class and class VIII.B as the control class. To collect data, researcher used multiple choice tests and pronunciation tests in pre-test and post-test. The data in this research were analyzed using T-test formula with the SPSS 26 program. The results showed that the mean post-test score for the experimental class (73.880) was significantly higher than the pre-test score (59.042), indicating that the chain spelling game positively affected vocabulary mastery. In conclusion, the use of chain spelling game had an effect to improve students' vocabulary.